Transforming the rural : global processes and local futures - Miele, Mara; Higgins, Vaughan, 1974-; Bjørkhaug, Hilde; Truninger, Mónica (Bingley, U.K. : Emerald Publishing Limited, 2017)
In recent decades, globalization has transformed rural societies and economies across the world. Much has been written by social scientists about the actors and structures underpinning these transformations and the effects on particular social groups, organizations and industries. Yet, to date much less attention has been given to the specific global processes that are fundamental to contemporary rural change. Rural Change and Global Processes provides a systematic analysis of the key global processes transforming rural spaces in the early 21st century financialization; standardization; consumption, and commodification. Through detailed case studies, the book examines why these processes are important, how they work in practice, and the challenges they raise as well as opportunities created. The book will be of particular relevance to researchers, graduate students, and policy-makers interested in the implications of global processes for rural people and livelihoods.
Prelims -- Financialization -- Standardization -- Commodification and consumption -- About the Authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Globalization -- Economic aspects; Rural population; Sociology, Rural; Social Science -- Sociology -- Rural; Rural communities